Effect of Infliximab in oxidised serum albumin levels during experimental colitis. (December 2014) - Cano-Martínez, David; Román, Irene D.; T. Lobo, M. Val; Pastor, Oscar; Moreno-Villena, Irene; Paradela, Alberto; Hernández-Breijo, Borja; Fernández-Moreno, Ma Dolores; Monserrat, Jorge; Sanmartín-Salinas, Patricia; Gisbert, Javier P.; Guijarro, Luis G.
Abstract Infliximab (IFX) is widely used in ulcerative colitis and in Crohn's disease treatment. Both diseases are characterised by increased oxidative stress, which may affect albumin oxidation. In order to test this hypothesis, the effect of IFX on colitis induced by dextran sulphate sodium (DSS) in rats was evaluated by measuring the Disease Activity Index, biochemical parameters, serum albumin oxidation and colonic mucosa oxidation. Rats with colitis showed an increase in oxidised serum albumin levels and in the oxidation of colon mucous cells. Both decreased after IFX treatment. This suggests that oxidised albumin could be a useful biomarker for monitoring inflammatory bowel disease.